DIGITALISASI DENAH RUANG KELAS SMA SINAR DHARMA DENGAN UNITY 3D - Tiga Wira Prasidya; Carisha Puspa Gozali; Darius Andana Haris (Jurnal Serina Abdimas, 2025)
Technological advancements have had a significant impact across various aspects of life, including entertainment, healthcare, and especially education. One of the most influential technological innovations is 3D (three-dimensional) visualization. 3D visualization is a method of representing images using three coordinate axes: X (length), Y (width), and Z (height). Unlike two-dimensional (2D) visualization, which only displays length and width, 3D visualization adds depth and volume, making objects appear more realistic and lifelike. This is achieved by implementing informatics knowledge into learning media based on Unity and 3D visual design. In addition, students are trained to work collaboratively to enhance communication and problem-solving skills. With the informatics background they have acquired, this technological theme is highly relevant and supports the school’s ongoing programs. Previously, a similar PKM (Student Creativity Program) activity had also been conducted in the form of assignments and Unity-based learning materials covering fundamental skills such as using ProBuilder to help students create floor plans. This activity was carried out through several stages, including needs assessment, material development, and task implementation. Therefore, it can be concluded that the activity ran successfully, had a positive impact on both parties, and provided tangible benefits for the development of students’ digital skills as well as for the partner institution. ABSTRAK Kemajuan teknologi telah memberikan dampak besar dalam berbagai bidang kehidupan, termasuk hiburan, kesehatan, dan terutama pendidikan. Salah satu inovasi teknologi yang cukup berpengaruh adalah Visual 3 Dimensi (3D), visual 3D merupakan metode representasi gambar menggunakan tiga sumbu koordinat: X (panjang), Y (lebar), dan Z (tinggi). Tidak seperti visualisasi dua dimensi (2D) yang hanya menampilkan panjang dan lebar, visual 3D mampu menghadirkan kedalaman dan volume, sehingga objek tampak lebih nyata dan realistis. Dengan cara mengimplementasikan pengetahuan informatika ke dalam media pembelajaran berbasis Unity dan desain visual 3D. Selain itu, siswa dilatih untuk bekerja secara kolaboratif guna meningkatkan keterampilan komunikasi dan pemecahan masalah. Dengan latar belakang pendidikan informatika yang telah diperoleh, tema teknologi ini sangat relevan dan mendukung kelangsungan program sekolah. Sebelumnya, kegiatan PKM serupa juga telah dilakukan dalam bentuk penugasan dan materi berbasis Unity yang terdiri dari ilmu dasar seperti menggunakan Probuilder untuk membantu murid membuat denah. Kegiatan ini dilaksanakan melalui beberapa tahapan, meliputi pengkajian kebutuhan, pengembangan materi, dan pelaksanaan tugas. Dengan demikian dapat disimpulkan bahwa kegiatan ini berjalan dengan baik, memberikan dampak positif untuk kedua belah pihak, dan memberikan manfaat nyata bagi pengembangan keterampilan digital peserta didik maupun institusi mitra.